International Trends Regarding Educational Equity from the Perspective of Educational Change - José Sánchez Santamaría; Asunción Manzanares Moya (Universidad Autónoma de Baja California, 2014)
Educational equity has become a social, political and scientific priority in many countries. This situation has gained momentum due to the increasing social and educational gaps in different countries around the World. It challenges the aspirations of modern Educational Policies to move forward towards more fair, cohesive and democratic society. Hence, this article puts into context and discusses the principal international trends on educational equity from the perspective of Educational Change. Therefore, a descriptive method focused on diachronic and hermeneutical approach with the analysis categories named as ways of change is carried out. A theoretical sample of documental sources is used. The results provide the existence of three trends from the 50s to the present: equal opportunities as educational access, equal opportunities as academic achievement/performance, and equity as inclusive and fair education. Now, there are two emerging trends under tension: educational excellence and educational justice.